Detection of Borax Content with Turmeric (Curcuma Longa Linn.) in Meatball Snacks in the Pekenan Area - Safitri, Riri (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Meatball snacks are one of the most popular culinary delights in Indonesia, nutrition in the form of animal protein which is important for the growth and development of our bodies can be obtained from consuming meatballs, but what is worrying is that there are irresponsible sellers who are not responsible for maintaining consumer health, namely adding borax as a food additive so that meatballs last longer and are more chewy, the use of borax in food can cause health problems. The Pekenan Pasar Sore area is an area that is one of the places where meatball sellers sell their wares, therefore the author conducted a study on the detection of borax content with turmeric filtrate in meatball snacks sold in the Pekenan Pasar Sore area, with the aim of finding out whether or not there are meatball sellers in the area who add borax to the ingredients for making their meatballs. This research was conducted from June to August 2024. This type of research is qualitative. The meatball samples in this study were meatballs from meatball traders in the Pekenan Pasar Sore area, Beringin District, totaling 12 traders taken by total sampling. Organoleptic tests and detection of borax content were carried out on meatball samples with turmeric filtrate. The data were analyzed descriptively. From the results of the study, it was found that the physical characteristics of the A-L meatball sample included having a natural meat aroma, gray color, and a texture that was not too chewy. And the results of the borax test on the A-L meatball sample with turmeric filtrate produced a yellow color. So from these results it shows that the A-L meatball sample sold by meatball sellers in the Pekenan Pasar Sore area does not contain borax.